The Action of Tick Extracts on Blood Coagulation and Fibrinolysis - Hellmann, K; Hawkins, Rosemary I (Thrombosis and Haemostasis, 1967)
Anticoagulant activity was found in the salivary glands, gut, eggs and coxal fluid of the tick O. moubata. The activity is due to antithrombin action in all 4 sources. A second anticoagulant was found in the salivary glands only, this was shown to have anti-factor IX action and is the first reported instance of such an activity extracted from a natural source.Fibrinolytic activity was found to be present in the gut, uterus, eggs and coxal fluid of O. moubata. This activity was shown to be a plasminogen activator which does not require a pro-activator and some of its physical characteristics were determined.Eggs of the tick D. andersoni were shown to have both antithrombin and plasminogen activator activity, but it was not possible to carry out detailed investigations on this material.